Effects of Mining Operations on Local Area Networks in Large Scale Gold Mining Environments in the Western Region of Ghana (Global Journal of Computer Science and Technology, 2014)
We investigate the impacts mining operations have on established Wired/Wireless Local Area Networks (WLANs) in mining environments in the Western Region of Ghana. Mining activities have certain immutable negative impacts on the topography of the land with consequent effects on LAN Networks. Notable are undulating landscape with pronounced physical obstructions, LAN infrastructural relocations and reconstruction, higher atmospheric dust concentration, severe ground vibrations due to blasting and the motion of heavy mine machineries. The mobile nature of mining operations/ practices often results in relocations of established network infrastructure such as fibre cables, repeater base stations, and mask towers (i.e. cell sites).The main reason for LAN infrastructural relocations is to ensure effective LAN/WLAN communication especially during mine expansions. However, this results into lengthy network downtimes. Employees2019; redundancies or idleness during network downtimes reduce mine productivity by about GHc2, 577, 860.64 (USD 1,288,930.32) annually. We recommend preventive maintenance schedule for all existing LAN infrastructure; basic Information Communication Technology (ICT) Training into the regular training module; technically qualified Information Technology (IT) experts be part of management and finally; IT projects be planned and integrated into the annual business plan. Netronics Wireless Broadband (NWB) communication technology solutions were also recommended to management and IT policy makers in the mining companies for consideration due to its good performance in mining environments.
Keywords: information communication technology; information technology; local area network; wired/wireless local area networks; intranets/extranets; infrastruct